Brand Awareness Dan Brand Image Sebagai Variabel Mediasi Pengaruh Social Media Marketing Terhadap Purchase Intention - Murtiningsih, Dewi; Pradopo, Loeky Rono; Supriyatno (LPPM Universitas 17 Agustus 1945 Semarang, 2025)
The purpose of this study is to determine the effect of social media marketing on purchase intention, to determine the effect of social media marketing on brand awareness, to determine the effect of brand awareness on purchase intention, to determine the role of brand awareness in mediating the influence to determine the effect of social media marketing on brand image, to determine the effect of brand image on purchase intention, to determine the role of brand image in mediating the influence to determine the effect of social media marketing on purchase intention. This study is included in the explanatory category. Determination of the number of samples using the MLE formula. The sampling technique uses simple random sampling. The number of samples in this study was 180 respondents. Data was processed using PLS. The results showed that social media marketing had no effect on purchase intention, media marketing had no effect on brand awareness, brand awareness had no effect on purchase intention, brand awareness did not mediate the influence of social media marketing on brand image, brand image had no effect on purchase intention, brand image did not mediate the influence of social media marketing on purchase intention.